Socio‐psychological impact of COVID‐19 on a diverse cohort of older adult research participants in New York. (December 2021) - Loizos, Maria; Sewell, Margaret; Neugroschl, Judith A; Zhu, Carolyn W; Li, Clara; Zeng, Xiaoyi; Pun, Kelly; Velasco, Nelly; Tocco, Carly; Sheppard, Faye; Ardolino, Allison; Meuser, Caroline; et al.
Abstract: Background: During the spring of 2020, New York was overwhelmed by COVID‐19 and older adults as well as ethnic minorities were disproportionately affected. The Alzheimer's Disease Research Center (ADRC) located in East Harlem in New York City, serves a predominantly low income, Latinx community. It was imperative to gauge the impact of COVID‐19 on our diverse group of older adult research participants. Method: Participants enrolled in the ADRC with a Clinical Dementia Rating Scale of 0 (75%) or .5 (24%) completed evaluations between May and December 2020 for the National Alzheimer's Cooperative Center Uniform Data Set (NACC UDS) and were administered a 33‐item COVID‐19 questionnaire over the telephone that was modified from the questionnaire provided by NACC. The 15–20 minute survey asked questions about social, psychological, and emotional experiences with COVID‐19, including whether they had lost a loved one to COVID, as well as items targeting the psychological sequelae of the pandemic (depression, isolation, a sense of loss of control, for example). Result: 198 participants completed the questionnaire. Of these, 55% were non‐Hispanic White, 15% were non‐Hispanic Black, 14% were Hispanic, and 16% were Asian. The overall sample's mean age was 76.4±7.5, mean education 15.80±3.1years, and 62.6% were male. Survey results indicated that 89% felt the pandemic had been disruptive to their lives, and 30% had lost a loved one to COVID. Sixty‐three percent of participants reported being in touch remotely with friends or family nearly every day, and 24% 2‐3x/week. Thirty two percent reported feeling they could not control important things in their life and feeling anxious (46%), bored (41%), and lonely (30%). Twenty seven percent reported feeling depressed and 23% experienced sleep problems. Conclusion: In this diverse sample of community dwelling older adults, most were able to remain in close contact with family and friends, and many reported the pandemic as disruptive. However, fewer reported experiencing a loss of control as well as psychological or emotional distress (i.e., depression) which may reflect adaptive mechanisms worthy of further study.